2010
DOI: 10.1016/j.jjcc.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Concentric left ventricular hypertrophy brings deterioration of systolic longitudinal, circumferential, and radial myocardial deformation in hypertensive patients with preserved left ventricular pump function

Abstract: C-LVH caused deterioration of the systolic longitudinal, circumferential, and radial myocardial deformation in patients with HT. LV torsion and circumferential shortening were considered to be compensatory mechanisms for maintaining LV pump function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
103
2
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 48 publications
(62 reference statements)
15
103
2
12
Order By: Relevance
“…Global LV peak early diastolic longitudinal strain rate may have provided more accurate assessment of LV diastolic function. Third, it has been reported that LV systolic function in the longitudinal direction is impaired in hypertensive patients with not only reduced EF but also preserved EF (Mizuguchi et al 2010). Therefore, data from agematched normal control group may be needed to clarify association between arterial stiffness and LV function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global LV peak early diastolic longitudinal strain rate may have provided more accurate assessment of LV diastolic function. Third, it has been reported that LV systolic function in the longitudinal direction is impaired in hypertensive patients with not only reduced EF but also preserved EF (Mizuguchi et al 2010). Therefore, data from agematched normal control group may be needed to clarify association between arterial stiffness and LV function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, data from agematched normal control group may be needed to clarify association between arterial stiffness and LV function. Finally, LV systolic function should be evaluated by the sum of longitudinal, circumferential, and radial deformation (Mizuguchi et al 2010). Further studies including data of LV longitudinal, circumferential, and radial directions may be needed to clarify association between CAVI and LV function.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) However, few data are available on use and outcome studied with conventional echocardiography in the evaluation of LA-LV interaction in asymptomatic patients in the community. Angle-independent two-dimensional speckle-tracking echocardiography (2DSTE) has recently been introduced into clinical practice because it offers early detection of impaired LA reservoir function 6,7) and LV contraction and relaxation 8,9) in subclinical patients with CVR factors. We hypothesized that comorbid conditions of CVR factors would be associated with worse LA-LV interaction, probably providing a potential explanation for the development to HFPEF in future.…”
Section: 2)mentioning
confidence: 99%
“…8,9) The basal short-axis view contained the mitral valve, the mid short-axis view contained the chordae tendineae, and the apical short-axis view was acquired distal to the papillary muscles. At each plane, 3 consecutive cardiac cycles were acquired at end-expiration breath holding and stored digitally on a hard disk for offl ine analysis.…”
Section: Wall Strainmentioning
confidence: 99%
“…13,14) Although there are studies that included circumferential or radial strain values, most were cross-sectional and did not examine intra-patient variation, which can be obtained only from serial echocardiography. [15][16][17][18][19][20] Among these cross-sectional studies, Kouzu, et al showed that LV radial strain was augmented to compensate for the decrease in longitudinal function and maintain stroke volume in early subclinical hypertensive heart disease. 21) Ng, et al reported that radial strain and strain rate were preserved in mild and moderate aortic stenosis and significantly decreased in severe AS.…”
Section: -7)mentioning
confidence: 99%